Buccal Fat Pad as a Potential Source of Stem Cells for Bone Regeneration: A Literature Review - Nasim Salehi-Nik; Maryam Rezai Rad; Lida Kheiri; Pantea Nazeman; Nasser Nadjmi; Arash Khojasteh (Hindawi Limited, 2017)
Adipose tissues hold great promise in bone tissue engineering since they are available in large quantities as a waste material. The buccal fat pad (BFP) is a specialized adipose tissue that is easy to harvest and contains a rich blood supply, and its harvesting causes low complications for patients. This review focuses on the characteristics and osteogenic capability of stem cells derived from BFP as a valuable cell source for bone tissue engineering. An electronic search was performed on all in vitro and in vivo studies that used stem cells from BFP for the purpose of bone tissue engineering from 2010 until 2016. This review was organized according to the PRISMA statement. Adipose-derived stem cells derived from BFP (BFPSCs) were compared with adipose tissues from other parts of the body (AdSCs). Moreover, the osteogenic capability of dedifferentiated fat cells (DFAT) derived from BFP (BFP-DFAT) has been reported in comparison with BFPSCs. BFP is an easily accessible source of stem cells that can be obtained via the oral cavity without injury to the external body surface. Comparing BFPSCs with AdSCs indicated similar cell yield, morphology, and multilineage differentiation. However, BFPSCs proliferate faster and are more prone to producing colonies than AdSCs.